2019
DOI: 10.1111/ijcp.13339
|View full text |Cite
|
Sign up to set email alerts
|

Fracture risk of young adults receiving proton‐pump inhibitors and H2‐receptor antagonists

Abstract: Summary Introduction Proton‐pump inhibitors (PPI) and histamine (type 2) receptor antagonists (H2RA) have the potential to interfere with calcium metabolism. Several authors have evaluated the effect of these medications on fracture incidence in older adults. A recent large epidemiologic study demonstrated a higher risk of fractures in young adults receiving PPI. Aim To evaluate the effect of PPI and H2RA use on fracture incidence in a large retrospective cohort of military recruits representative of general p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
(54 reference statements)
1
6
0
1
Order By: Relevance
“…Recently one cohort study conducted by Fedida et al published in International Journal of Clinical Practice revealed that no significant association could be detected between proton pump inhibitors use and fracture risk in young adults. 1 The similar finding was also observed in older adults. 2,3 Some points need to be discussed.…”
Section: Proton Pump Inhibitors Use and Fracture Risk In Young Adultssupporting
confidence: 75%
See 1 more Smart Citation
“…Recently one cohort study conducted by Fedida et al published in International Journal of Clinical Practice revealed that no significant association could be detected between proton pump inhibitors use and fracture risk in young adults. 1 The similar finding was also observed in older adults. 2,3 Some points need to be discussed.…”
Section: Proton Pump Inhibitors Use and Fracture Risk In Young Adultssupporting
confidence: 75%
“…First, the relative risk of fracture was lower in young male adults with proton pump inhibitors use than those without use in Fedida et al’s study (relative risk 0.73) . In a crude estimation, the incidence of fracture risk was lower in young male adults with proton pump inhibitors use than those without use (180.6 vs 377.7 per 10 000 patient‐years) . The absolute risk reduction was approximately 197.1 per 10 000 patient‐years of follow‐up.…”
mentioning
confidence: 90%
“…Moreover, use of PPIs may also increase risk of falls [ 291 , 292 , 293 ]. These associations, however, have not been confirmed in a number of longitudinal studies and reviews [ 259 , 280 , 294 , 295 , 296 , 297 , 298 , 299 , 300 , 301 , 302 , 303 , 304 , 305 , 306 , 307 , 308 , 309 ]; even a modest reduction in fracture risk with PPI use has been reported [ 307 , 310 ]. Some researchers who are not supporting the association of PPI therapy with BMD recognize, nevertheless, that in PPI users the risk of fractures and falls could be higher [ 311 , 312 ] as the unadjusted HR was significantly elevated (1.36, 95% CI 1.19–1.55).…”
Section: Hpi-induced Upper Gut Diseases and Osteoporotic Fracturesmentioning
confidence: 99%
“…Six studies (Freedberg et al, 2015a;Fedida et al, 2019;Malchodi et al, 2019;Wagner et al, 2019;Fleishman et al, 2020;Wang et al, 2020) were included in our meta-analysis following the abovementioned exclusion and selection procedure. The main characteristics of the included studies are summarized in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%